Analysis of anthropometric characteristics in young table tennis players - De La Torre, A. I.; Pradas, F.; Salvà, P.; Castellar, C.; González-Jurado, J. A. (Proceedings Book of The 15th ITTF Sports Science Congress Düsseldorf, 27th - 28th May 2017, 2017)
The purpose of this study is to evaluate how the measured anthropometric characteristics evolved in young table tennis players as a consequence of a specific training regime. 41 players took part in this study (12 female and 29 male) all of whom underwent control and evaluation for a period of four years (between the ages of 9 and 12). Anthropometric evaluation was conducted following the International Society for The Advancement of Kinanthropometry protocol. Data collected for body variables were: weight, height, BMI, skinfolds (biceps, triceps, subscapular, supraspinale, iliac crest, mid thigh and calf), perimeters (contracted/relaxed arm an leg), diameters (humerus, styloid and bicondyle of femur). Body composition was calculated using percentage of body fat, bone and mass percentage, following De Rose and Guimaraes` tetracompartmental model. Carter`s method was used to obtain somatotype. Consent form was signed by all participants prior to fore-mentioned processes being carried out. Analysis of variance for repeated measures of a single factor showed statistically significant differences for BMI (p=0.029) and for total value of six skin-folds (p=0.015), increasing in both cases with age. No statistically significant differences were found in reference to muscle and fat mass percentages. Total value of six skin-folds and BMI are extremely interesting variables to keep in mind when managing the evolution of an athlete`s biotype due to the direct accumulative effect of specific training sessions after several years. Evaluating body composition in young players may be of interest when it comes to managing their progression, maturation and both physical and sports performance.